Student satisfaction and intention to recommend a TESOL program in a Global South context: Evidence from Indonesian English language education students - Paulus Widiatmoko; Anesti Budi Ermerawati; Ignatius Tri Endarto (Universitas Muhammadiyah Malang, 2026)
As part of the Global South, Indonesia has long integrated TESOL program into its education to prepare English language teachers that are competent. Despite the huge number of TESOL programs currently offered by Indonesian universities, research on service quality evaluation models for pre-service English teacher education in Indonesia is still quite limited. For that reason, this study examines how perceived service quality shapes student satisfaction and intention to recommend an English Language Education program within a Global South TESOL context in Indonesia. The objectives of this are: (1) to assess the validity and reliability of the student service quality assessment model; (2) to evaluate the association between service quality factors and student satisfaction; and (3) to determine the connection between satisfaction and students' intention to endorse the English teacher education program. Using an exploratory sequential mixed-method design, the research first generated qualitative insights to construct context-appropriate indicators of students’ quality perceptions and to inform survey instrument development. The validated questionnaire was distributed to 92 Indonesian undergraduate students, and data were analyzed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The results demonstrated satisfactory validity, reliability, and model fit. Path analysis revealed significant positive effects of facility quality and interpersonal relationships on student satisfaction and their willingness to recommend the program. These findings highlight the importance of strengthening student experience in Indonesian English teacher education, offering empirical evidence relevant to quality enhancement efforts across Global South TESOL programs.